Implications of Direct Regional Head Elections: Independent vs. Political Party Candidates in Metro City, Lampung Province - Fajar Riatama; Djohermansyah Djohan; Nurliah Nurdin; Yudi Rusfiana (Yayasan Riset dan Pengembangan Intelektual, 2023)
The phenomenon that is the object of research is the contestation of direct regional head elections for independent candidate pairs versus political party candidate pairs and the continuity of government after the regional head elections in Metro City, Lampung Province, phenomenally won by independent candidate pairs. This study aims to analyze the contestation of independent candidate pairs versus political party candidate pairs in Metro City in the 2020 regional elections won by independent candidates; develop a strategy for independent candidate pairs winning the 2020 regional election contestation to maintain the continuity of government after the regional head elections. This research method uses descriptive qualitative methods with 4 research informants. The results of the study can be concluded that the victory of individual candidate pairs in the contestation of Pilkada in Metro City in 2020 analyzed by referring to Bourdie's Capital Theory is still felt less than optimal, because individual candidate pairs do not get political support from political actors in Metro City. Political Capital Theory is seen as very weak. As a real strategy, each individual candidate pair must have Reputation Capital as the main capital for candidates through individual channels. The continuity of the government after the victory of the individual candidate pairs that lack support from the Legislative Members can apply a persuasive communication approach strategy by prioritizing the Community of People, Attempted Influence, Beliefs, Values and Attitude as the main basis for running the government.